Identification of a Putative Binding Site for Negatively Charged Surfaces in the Fibronectin Type II Domain of Human Factor XII - Citarella, Franca; te Velthuis, Henk; Helmer-Citterich, Manuela; Hack, C. Erik (Thrombosis and Haemostasis, 2000)
Monoclonal antibodies directed against functional sites of proteins provide useful tools for structure-function studies. Here we describe a mAb, KOK5, directed against the heavy chain region of human coagulation factor XII (FXII), which inhibits kaolin-induced clotting activity by preventing the binding of FXII to kaolin. Furthermore, mAb KOK5 enhances FXII susceptibility for cleavage by kallikrein and supports FXII autoactivation. Hence, mAb KOK5 likely is directed against the binding site of FXII for negatively charged surfaces. Screening of two phage-displayed random peptide libraries with mAb KOK5 selected phages that could be grouped on the basis of two amino acid consensus sequences: A) FXFQTPXW and B) HQ/LCTHR/KKC. Sequence A contains two motifs: one shares homology with FXII amino acid residues 30-33 (FPFQ), the second one with residues 57-60 (TPNF); both amino acid stretches belonging to the fibronectin type II domain of FXII. Sequence B also reveals homology with part of the fibronectin type II domain, i.e. the stretch 40-47 (HKCTHKGR). A three-dimensional model of FXII residues 28-65, obtained by homology modeling, indicated that the three amino acid stretches 30-33, 40-47 and 57-60 are close to each other and accessible for the solvent, i.e. in a form available for interaction with the monoclonal antibody, suggesting that mAb KOK5 recognizes a discontinuous epitope on the fibronectin type II domain of FXII. Peptides corresponding to FXII sequences 29-37 (FXII29-37) or 39-47 (FXII39-47), were synthesized and tested for the capability to inhibit FXII binding to negatively charged surfaces. Peptide FXII39-47 inhibited the binding of labeled FXII to kaolin and effectively prevented both dextran sulfate-and kaolin-induced activation of the contact system in plasma. Hence, we suggest that the fibronectin type II domain of FXII, in particular residues 39 to 47, contribute to the binding site of FXII for negatively charged surfaces.
Keywords: Factor XII; binding site; fibronectin type II